Hubungan antara Authentic Leadership dan Resiliensi pada Karyawan : Peran Mediasi Kepuasan Kerja di Perusahaan Multinasional di Wilayah Semarang - Puspita Puji Rahayu; Ervina Kumalasari; Benedicta Audrey Putri Trisnadewi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the relationship between Authentic Leadership, Organizational Support, and Job Demands on Employee Resilience, with Job Satisfaction serving as a mediating variable. The research focuses on employees of multinational companies in Semarang, utilizing a quantitative approach with regression analysis to evaluate direct, indirect, and interaction effects among the variables.The findings reveal that Authentic Leadership does not significantly influence Employee Resilience directly, though it demonstrates a positive trend, indicating its potential role in creating a supportive work environment for resilience development. Similarly, Organizational Support shows no significant direct effect on Employee Resilience, suggesting that individual perceptions of organizational support may be influenced by other unexamined factors. Job Demands, while having a positive relationship with Employee Resilience, are also not statistically significant, implying that well-managed work demands may positively contribute to resilience without imposing excessive stress.Job Satisfaction as a mediating variable does not significantly explain the relationship between independent variables and Employee Resilience. Additionally, the interaction effects between Job Satisfaction and the independent variables (Authentic Leadership, Organizational Support, and Job Demands) are not significant. These findings suggest that while Job Satisfaction remains essential, its mediating or moderating role in this context is limited.Nevertheless, the overall regression model, which incorporates all variables and interactions, is statistically significant (F = 16.369; p < 0.001), indicating that the combination of these factors collectively influences Employee Resilience. This highlights the importance of considering multiple organizational factors to enhance employee adaptability and productivity.